Investigation and control of laser pointing fluctuations on stability of terahertz time domain spectrometer. (31st January 2022) - Mumtaz, Muhammad; D Khan, Sabih; Aslam Zia, M; Shahzad, Arslan; Ahmad, Izhar
Abstract: Terahertz time domain spectroscopy (THz-TDS) is a well known technique for analyzing materials in terahertz regime. The stability and reproducibility of the THz signal amplitude is most crucial for reliable measurements using this technique. In this article, an extensive investigation on the origin and the impact of beam pointing fluctuations on amplitude of THz signal is performed. These fluctuations have been reduced to minimum level with control on sources of beam pointing fluctuation including air turbulences and temperature drifts. Under these controlled conditions, the standard deviation in the measurement of refractive index and absorption coefficient have been reduced up to 1.3 × 10 − 4 and 0.2 cm −1, respectively.